2015
DOI: 10.1039/c5cc00178a
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic benzylic C–H bond oxidation with a flavin scandium complex

Abstract: The enhanced reduction potential of riboflavin tetraacetate coordinating to scandium triflate enables the challenging photocatalytic C-H oxidation of electron-deficient alkylbenzenes and benzyl alcohols.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 26 publications
0
60
0
1
Order By: Relevance
“…Some derivatives were also immobilized on silica gel and applied in the oxidation of benzyl alcohols [13]. Furthermore, it was shown that the oxidation power of RFTA can be increased by coordination to scandium triflate [14]. Recently, the E / Z -isomerization of olefins with riboflavin as catalyst was reported [15], which was also used for cyclization to form coumarins [16].…”
Section: Resultsmentioning
confidence: 99%
“…Some derivatives were also immobilized on silica gel and applied in the oxidation of benzyl alcohols [13]. Furthermore, it was shown that the oxidation power of RFTA can be increased by coordination to scandium triflate [14]. Recently, the E / Z -isomerization of olefins with riboflavin as catalyst was reported [15], which was also used for cyclization to form coumarins [16].…”
Section: Resultsmentioning
confidence: 99%
“…Because the E red * of 1 (RFl‐2Sc 3+ )* is 2.45 V versus SCE, which is higher than the one‐electron oxidation potential of toluene (2.20 V vs. SCE), the photocatalytic oxidation of toluene by O 2 occurs efficiently by using RFl‐2Sc 3+ as a photocatalyst to yield benzaldehyde (71 % yield). However, no photocatalytic oxidation of toluene by O 2 occurs in the presence of RFl without Sc 3+ …”
Section: Flavin Photoredox Catalystsmentioning
confidence: 99%
“…In addition, a series of elegant methods were successfully applied to construct C=O, C=C, and C=N double bonds (Scheme B). The direct oxidation of benzylic C(sp 3 )—H bond to aryl ketone was the most common . In 2012, Zhang and Patel accomplished a Pd‐catalyzed benzylic C(sp 3 )—H arylation/oxidation reaction.…”
Section: Background and Originality Contentmentioning
confidence: 99%